To design a pure bending testing fixture / Syed Mohd Nazri Syed Aziz and Norizan Bahari - Syed Aziz, Syed Mohd Nazri; Bahari, Norizan (1994)
This project is taken as an alternative of pure bending testing which Shimadzu machine have some problems. The task, as far as the design is concerned is to match with the Instron dynamic machine 8032 and of course the dynamic loading will be a consideration. The chosen of the suitable material are also the important part. The safety for the operator must be the first part that have to take as a concentration. The designers have to find the best solution in order to get the best result so that the project will be categorized as a success.